c.1 - Anirudh prasad (New Delhi, 1980)
Social Justice is the signature tune of the Indian Constitu tion. This founding faith has paramount position in our society because the struggle for freedom has been not only political but economic and social. Gandhi, Nehru, Ambedkar and every other great Indian has visualised the imperatives of Independence as implying an integral approach and the Constituent Assembly, when it set its final seal on the Nation al Charter, did harken to the holistic nature of social, eco nomic and political equality if democracy were to be stable. The explosive pervasiveness of appalling economic privations and social suppressions made this key-note thought the most profound ideology of the Constitution. That is why, running right through the warp and woof of the country's Funda mental Law, we find a great concern for the weaker sections of the community. The masses have suffered social injustice too long and been separated by the Poverty Curtain too strong that if peaceful transformation of the nation into an egalitarian policy were not achieved, chaos, upsurge and massive disruptions would destroy the peaceful progress which is Freedom's tryst with Indian destiny.
Keywords: Law- India .